122k views
3 votes
Use the zero product property to find the solutions to the equation (x + 2) (x + 3) = 12.

User Qitch
by
4.6k points

2 Answers

3 votes
The answer is 2 fishing method and divide both sides by 6
User Alex Avrutin
by
4.4k points
3 votes

Answer:


x_(1) =-6\\x_(2) =1

Explanation:

The given equation is


(x+2)(x+3)=12

First, we need to apply distributive property to have the quadratic expression


x^(2) +3x+2x+6=12\\x^(2) +5x+6-12=0\\x^(2) +5x-6=0

We need to find two numbers which product is -6 and which difference is 5. Those numbers are 6 and 1, because 6 - 1 = 5, and 6(-1) = -6.


x^(2) +5x-6=(x+6)(x-1)=0

If we apply the zero product property, that means each binomial is equal to zero


x+6=0\\x-1=0

Therefore, the solutions are


x_(1) =-6\\x_(2) =1

User Kmkemp
by
4.9k points